Laser-driven strong magnetostatic fields with applications to charged beam transport and magnetized high energy-density physics - Santos, J; Bailly-Grandvaux, M; Ehret, M; Arefiev, A; Batani, D; Beg, F; Calisti, A; Ferri, S; Florido, R; Forestier-Colleoni, P; Fujioka, S; Gigosos, M; et al. (AIP Publishing, 2018)
Powerful laser-plasma processes are explored to generate discharge currents of a few 100 kA in coil targets, yielding magnetostatic fields (B-fields) in excess of 0.5 kT. The quasi-static currents are provided from hot electron ejection from the laser-irradiated surface. According to our model, which describes the evolution of the discharge current, the major control parameter is the laser irradiance Ilasλ 2 las. The space-time evolution of the B-fields is experimentally characterized by high-frequency bandwidth B-dot probes and by protondeflectometry measurements. The magnetic pulses, of ns-scale, are long enough to magnetize secondary targets through resistive diffusion. We applied it in experiments of laser-generated relativistic electron transport through solid dielectric targets, yielding an unprecedented 5-fold enhancement of the energy-density flux at 60 µm depth, compared to unmagnetized transport conditions. These studies pave the ground for magnetized high-energy density physics investigations, related to laser-generated secondary sources of radiation and/or high-energy particles and their transport, to high-gain fusion energy schemes and to laboratory astrophysics.